SOME CLASSES OF ALMOST CONVERGENT PARANORMED SEQUENCE SPACES DEFINED BY ORLICZ FUNCTIONS - Isik, Mahmut (De Gruyter Poland Sp Zoo, 2012)
In this paper we define l(infinity)( M, p, phi, q, s), c( M, p, phi, q, s) and c(0)( M, p, phi, q, s), the sequence spaces on a seminormed complex linear space, using an Orlicz function. We give various properties and some inclusion relations on this space.
Keywords: Orlicz function; invariant mean; seminorm